Endothelial dysfunction assessment by noninvasive peripheral arterial tonometry in patients with chronic obstructive pulmonary disease compared with healthy subjects. (16th August 2017) - Malerba, Mario; Radaeli, Alessandro; Nardin, Matteo; Clini, Enrico; Carpagnano, Giovanna Elisiana; Sciatti, Edoardo; Salghetti, Francesca; Bonadei, Ivano; Platto, Fabio; Vizzardi, Enrico
Abstract: Introduction: Patients with chronic obstructive pulmonary disease (COPD) have an increased risk of cardiovascular disease. The endothelial dysfunction likely plays a central role in increasing cardiovascular risk. Objectives: This cross‐sectional, study investigated the prevalence and extent of endothelial dysfunction in patients with stable COPD. Methods: Peripheral arterial tonometry (PAT) was measured by post‐ischemic reactive hyperemia index (RHI) in 16 COPD patients, 16 healthy controls and 16 subjects with treated systemic arterial hypertension (AH) and analysed with covariates condition (dyslipidemia, and medications). Results: The prevalence of endothelial dysfunction was significantly higher in COPD group than in the other groups. Mean RHI was significantly lower in COPD patients compared with the other groups. At linear regression FEV1 and RHI were directly correlated (Spearman index = 0.553; P = .026). COPD patients in groups C and D according to Global Initiative for Chronic Obstructive Lung Disease (GOLD) stages showed lower RHI compared with patients classified as A and B ( P < .01). At multiple regression analysis the presence of dyslipidemia, COPD and AH were associated with the presence of endothelial dysfunction. Conclusions: Endothelial dysfunction in stable COPD patients is probably implicated in the high cardiovascular comorbidity. This study suggests the potential utility of endothelial dysfunction evaluation in patients with COPD to a timely assessment and treatment for cardiac complications.